2016
DOI: 10.1002/glia.23007
|View full text |Cite
|
Sign up to set email alerts
|

Critical data‐based re‐evaluation of minocycline as a putative specific microglia inhibitor

Abstract: Main Points:-Minocycline is not a specific microglia inhibitor -Minocycline has bona fide effects on neuroinflammation in vivo -Data generated with minocycline are difficult to interpret

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
106
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 98 publications
6
106
1
Order By: Relevance
“…Supporting our observation, MC has numerous effects on various cell types other than microglia (Moller et al, 2016) and has been reported to have direct neuroprotective action (Kraus et al, 2005;Schildknecht et al, 2011;Shimazawa et al, 2005). Supporting our observation, MC has numerous effects on various cell types other than microglia (Moller et al, 2016) and has been reported to have direct neuroprotective action (Kraus et al, 2005;Schildknecht et al, 2011;Shimazawa et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Supporting our observation, MC has numerous effects on various cell types other than microglia (Moller et al, 2016) and has been reported to have direct neuroprotective action (Kraus et al, 2005;Schildknecht et al, 2011;Shimazawa et al, 2005). Supporting our observation, MC has numerous effects on various cell types other than microglia (Moller et al, 2016) and has been reported to have direct neuroprotective action (Kraus et al, 2005;Schildknecht et al, 2011;Shimazawa et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…and (b) [Color figure can be viewed at wileyonlinelibrary.com] (Figure 4c), similar to the previous report(Ebneter, Kokona, Jovanovic, & Zinkernagel, 2017). NMDA dramatically increased microglial number in AIN-treated mice but not in PLXtreated mice.As described earlier, because MC may have direct neuroprotective potentials(Moller et al, 2016;Shimazawa et al, 2005), we further evaluated microglia-independent effect by MC. NMDA dramatically increased microglial number in AIN-treated mice but not in PLXtreated mice.As described earlier, because MC may have direct neuroprotective potentials(Moller et al, 2016;Shimazawa et al, 2005), we further evaluated microglia-independent effect by MC.…”
mentioning
confidence: 99%
“…Additionally, we showed enhanced microglial contact with POMC cell soma and decreased hypothalamic POMC cell number, which was reversed by the co-treatment with a microglial activation blocker minocycline. Although minocycline is not a selective microglia blocker [29], it has a significant inhibitory effect on the inflammatory phase of microglia [30]. We have used minocycline to determine its ability to block microglia-mediated ethanol action on POMC cells in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tadmouri et al (2014) used immunohistochemistry to show that microglia and astrocytes in the NTS were activated by 24 hours of CSH, with astrocyte activation peaking at 6 hours, followed by microglia at 24 hours of CSH. They also showed that systemic administration of minocycline, which inhibits microglia among other effects (Moller et al, 2016), blocked a time-dependent increase in ventilation observed following 24 hours of CSH, as well as immunohistochemical signals for microglia activation (Tadmouri et al, 2014). MacFarlane et al (2015) also found that CSH (5 days) increased expression of microglia in the NTS and dorsal motor nucleus of the vagus, and this change was blocked by minocycline.…”
Section: Cns Inflammation and Neuroplasticitymentioning
confidence: 97%
“…However, further experiments are necessary to determine the exact effects of minocycline (cf. Moller et al, 2016), the relative roles of microglia versus astrocytes and if the sequence of their activation is important as suggested by Tadmouri and co-workers (2014).…”
Section: Cns Inflammation and Neuroplasticitymentioning
confidence: 99%